2011
DOI: 10.1177/0363546511417573
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Bioabsorbable Suture Anchors in the Shoulder

Abstract: The development of the suture anchor has played a pivotal role in the transition from open to arthroscopic techniques of the shoulder. Various suture anchors have been manufactured that help facilitate the ability to create a soft tissue to bone repair. Because of reported complications of loosening, migration, and chondral injury with metallic anchors, bioabsorbable anchors have become increasingly used among orthopaedic surgeons. In this review, the authors sought to evaluate complications associated with bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 56 publications
1
84
1
1
Order By: Relevance
“…The pullout strength obtained in that study was lower, but this is probably related to the nature of the support (bovine tuberosity in our study; porcine femoral diaphysis in the Barber et al [9,17] studies). During SA failure (anchor detachment or eyelet rupture), the release of intra-articular foreign bodies (anchor fragments) can have adverse effects, especially on cartilage [10][11][12][13][14]. For ASAs, it is likely that the complications of failure are mild and comparable with those of a transosseous suture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pullout strength obtained in that study was lower, but this is probably related to the nature of the support (bovine tuberosity in our study; porcine femoral diaphysis in the Barber et al [9,17] studies). During SA failure (anchor detachment or eyelet rupture), the release of intra-articular foreign bodies (anchor fragments) can have adverse effects, especially on cartilage [10][11][12][13][14]. For ASAs, it is likely that the complications of failure are mild and comparable with those of a transosseous suture.…”
Section: Discussionmentioning
confidence: 99%
“…Anchors require surgical preparation of the bone insertion site (drilling or punching), and their size (up to 6.5 mm) limits the number of anchors on the insertion site, which can lead to bone loss and result in imprecise tendon reinsertion. Finally, interarticular migration (of the entire anchor or fragments), prominent intra-articular portions and resorption granuloma fractures have been described in anchor failures [10][11][12][13][14]. Due to the volume and reported complications of anchors, some surgeons prefer to repair the rotator cuff with transosseus points, allowing a very small gap between attachment points without using anchors [15].…”
Section: Introductionmentioning
confidence: 99%
“…Implant selection plays an important role in potential complications. Anchor usage can lead to significant pain, decreased ROM, and failure if they are not positioned properly during the initial procedure [40]. Degenerative joint conditions, such as chondrolysis and osteoarthritis (OA), have also been reported as long-term complications of arthroscopic Bankart repair, primarily due to intra-articular pain pumps, which have since fallen out of favor.…”
Section: Complicationsmentioning
confidence: 99%
“…Additionally, arthroscopic repair of torn acetabular labrum is on the rise and suture anchors are used to re-approximate the torn tissue. The majority of suture anchors for these applications are currently made of polymers, and it has been shown that these devices may cause osteolysis leading to osseous cyst formation (Dhawan et al, 2012). Excellent biocompatibility and osteoinductivity of Mg and its alloys may allow better bone healing.…”
Section: Future Developmentsmentioning
confidence: 99%